Unraveling the metabolic effects of benzophenone-3 on the endosymbiotic dinoflagellate Cladocopium goreaui - Zhang, Kaidian; Shen, Zhen; Yang, Weilu; Guo, Jianing; Yan, Zhicong; Li, Jiashun; Lin, Jiamin; Cao, Xiaocong; Tang, Jia; Liu, Zhaoqun; Zhou, Zhi; Lin, Senjie (Frontiers in Microbiology, 2023)
As a well-known pseudo-persistent environmental pollutant, oxybenzone (BP-3) and its related organic ultraviolet (UV) filters have been verified to directly contribute to the increasing mortality rate of coral reefs. Previous studies have revealed the potential role of symbiotic Symbiodiniaceae in protecting corals from the toxic effects of UV filters, however the detailed protection mechanism(s) have not been explained. Here, the impacts of BP-3 on the symbiotic Symbiodiniaceae Cladocopium goreaui were explored. C. goreaui cells exhibited distinct cell growth at different BP-3 dose, with increased growth at the lower concentration (2 mg L-1) and rapid death at higher concentration (20 mg L-1). Furthermore, C. goreaui cells showed a significant BP-3 uptake at the lower BP-3 concentration. BP-3 absorbed cells exhibited elevated photosynthetic efficiency, and decreased cellular carbon and nitrogen contents. Besides, the derivatives of BP-3 and aromatic amino acid metabolism highly responded to BP-3 absorption and biodegradation. Our physiological and metabolic results reveal that the symbiotic Symbiodiniaceae could resist the toxicity of acceptable range of BP-3 through promoting cell division, photosynthesis, and reprogramming amino acid metabolism. This study provides novel insights into the influences of organic UV filters to coral reef ecosystems, which urgent needs increasing attention and management.